Design of a high temperature (1350 °C) solar receiver based on a liquid metal heat transfer fluid: Sensitivity analysis. (April 2018) - DeAngelis, Freddy; Seyf, Hamid Reza; Berman, Rebecca; Schmidt, Greg; Moore, Duncan; Henry, Asegun
Highlights: A high-temperature liquid metal solar thermal cavity receiver was analyzed. Cavity convection and location of hot spots can significantly impact efficiency. Thermal stresses must be carefully managed for such a receiver. It is feasible to reach temperatures of 1350 °C at ≥90% efficiency. Abstract: One approach to reducing the cost of concentrated solar power is to improve the heat engine efficiency by increasing its maximum operating temperature. To achieve higher operating temperatures, we have studied using a liquid metal heat transfer fluid in conjunction with a receiver made from a ceramic/refractory material. As a first step in the design of such a receiver, we conducted sensitivity analyses of several receivers, allowing us to determine what factors most significantly affect receiver performance. Material properties, natural convection from the receiver cavity, and the location of hot spots within the cavity were found to have the largest effect on receiver efficiency. It was also determined that stresses due to thermal expansion can exceed the fracture strength of the receiver material if care is not taken to minimize these stresses. Interestingly, the stress as opposed to performance considerations, set the most important constraints on the receiver geometry.